(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides ideas about independent artistic activity that occurs on the initiative of preschool children, pedagogical guidance of this activity, and the formation of a child’s interest in artistic activity by creating a comfortable teaching environment.